Pembuatan Virgin Coconut Oil (VCO) Pada Kegiatan Belajar Dan Pendampingan Masyarakat Di Desa Oeletsala - Jofret Umbu Soru Peku Djawang; Alya Elita Sjioen; Maromi Merlin Mbate; Jusuf Aboladaka; Anggelina Dasilva Mali (Jurnal Pengabdian Masyarakat, 2023)
Oeletsala Village also has several excellent potentials in the plantation sector which can be managed as a source of increasing the income of the village community, one of which is coconuts which are very abundant, where almost every community house in Oeletsala Village has coconut trees that thrive. The local people are still not aware of utilizing the potential of coconuts and lack of knowledge in the process of producing coconuts into a product that has a high selling value such as Virgin Coconut Oil (VCO), so many coconuts are wasted. The solution offered to partners in solving the problem is to conduct training on making Virgin Coconut Oil (VCO) for the people of Oeletsala Village, in this case youth groups, representatives of disability groups and Oeletsala Village officials, thereby increasing people's income and training partners in utilizing online media as a means of to sell and promote VCO products, with the expected outcome through this activity is the creation of a Virgin Coconut Oil (VCO) product that is packaged in an attractive way and determines the selling price and the use of online marketing media such as Facebook, Instagram and Whatsapp as a means of product marketing.